Sobel and Canny Edges Segmentations for the Dental Age Assessment - Razali M.R.M.; Ahmad N.S.; Hassan R.; Zaki Z.M.; Ismail W. (Institute of Electrical and Electronics Engineers Inc., 2024)
Indexed by SCOPUS/WOS